The State obligation to respect, protect and fulfill economic, social and cultural rights in the context of business activities - Nabwowe Kasule, Angella; Mncwabe, Nokukhanya (Initiative for Social and Economic Rights (ISER), 2017)
Uganda has embarked on an ambitious programme to become an upper middle-income country by 2020.1 In line with this agenda, the National Development Plan (NDP II) prioritizes private sector led economic growth — particularly in the agricultural, tourism and, most notably, extractive sectors, (since the discovery of oil in western Uganda is expected to have a huge impact on the economy).